Sustaining the Melanau language / Mohamad Musa Bohari - Bohari, Mohamad Musa (UiTM Cawangan Sabah, 2021)
This paper proposes a strategy to sustain the Melanau language. The justification for sustaining the language includes possibilities of language endangerment which has destroyed thousands of languages of the world. The Melanau language which covers multiple dialects is exposed to many threats such as attitudes towards the language and dominant languages, especially in dealing with the forces of globalization. Therefore, the strategy to sustain the Melanau language includes programmes of documentation, promoting the language into cyberspace and media, the revival of art and literature, and the introduction of the language to the national academic setting. It needs to be implemented by various parties, especially the speakers of Melanau themselves. However, the sustainability effort might face challenges particularly involving multiple Melanau dialects. Thus, this situation deserves careful attention from all the Melanau speech communities.